Hành vi bán hàng phi đạo đức: Khám phá vai trò của sự tập trung phúc lợi của khách hàng - Nguyễn Thị, Hồng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study aims to examine the influences of performance goal attributes (e.g., difficulty, specificity, and performance pressure), cognitive factors reflect individual’s self-control capacity (e.g., customer stewardship control, and moral justification), and working environmental factors (e.g., peer’s unethical sales behavior and perceived group creativity) on unethical selling behavior in the sales context. Data was collected from salespeople who are working for a variety of companies in Vietnam. Partial Least Squares Structural Equations Modeling (PLS-SEM) and SmartPLS 3 were implemented to test the research model. The findings indicate that performance goal attributes negatively influence on customer stewardship control and positively influence on unethical selling behavior. Thus, highlighting the mediating and moderating roles of the customer stewardship control, this paper contributes to deeply understanding about ethical erosion in people’s cognition and proposes governance implications for businesses and enterprises